A Modal Description of Multiport Antennas - Jonathan J. Lynch (International Journal of Antennas and Propagation)
This paper presents a modal description of multiport antennas that leads directly to a rigorous network representation and simple quadratic expressions for gain, efficiency, and effective area. The analysis shows that the transmitting and receiving properties of an 𝑁 element antenna array are exactly described by a 2𝑁×2𝑁 element scattering matrix together with a set of 𝑁 orthonormal mode functions and accounts for effects such as mutual coupling, scattering, reflection, and losses. The approach is quite general, only requiring that the antenna be finite and reciprocal. The scattering network description simplifies accounting of power flow while retaining a close connection to the physical antenna characteristics. The orthonormal mode functions provide a complete basis for radiated and received fields, facilitating beamforming. The theory provides rigorous definitions of input-output signals and links them to the underlying electromagnetics in a straightforward manner.